The Molecular Simulation Study of nNOS Activation Induced by the Interaction Between Its Calmodulin-Binding Domain and SUMO1 - Wang, Nan; Hou, Xiao-Yu (Frontiers in Molecular Neuroscience, 2020)
Neuronal nitric oxide synthase (nNOS), an enzyme required for learning and memory, catalyzes L-arginine decomposition during nitric oxide production in mammalian neurons. Over-activation of nNOS leads to oxidative/nitrosative stress, which is part of the pathophysiological process of various neuropsychiatric disorders. Previous experimental studies suggest that nNOS is a target for small ubiquitin-like modifier 1 (SUMO1), and that SUMO1-ylation upregulates nNOS catalytic activity in hippocampal neurons. To date, a comprehensive structural model has not been proposed for nNOS SUMO1-ylation. In this study, our aim was to build in silico models to identify the non-bonded interactions between SUMO1 and the calmodulin binding domain (CaMBD) of nNOS. Using molecular docking and molecular dynamics simulation, we found that SUMO1 modification stabilizes the conformation of nNOS CaMBD, and helps maintain a conformation beneficial for nNOS catalysis. Analysis of the polar contacts and hydrogen bonds, and the root mean square derivation results showed that, R726 and R727 of CaMBD formed polar contacts or high occupancy hydrogen bonds with SUMO1. Correlation factor analysis and free energy calculations showed that the W716, L734, F740, M745, and F781 residues were also involved in the SUMO1/CaMBD interaction in an orientation-dependent manner. The potential inhibitor binding pocket of SUMO1, aimed at disrupting SUMO1/CaMBD binding, was detected from the virtual screening results. Our in silico studies revealed that interfering with the non-bonded interactions of SUMO1/CaMBD would blocked nNOS SUMOylation and subsequent hyperactivation. This work provides novel structural insight into the functional regulation of nNOS by post-translational SUMO1 modification, and provides suggestions for the design of drugs targeting nNOS hyperactivation.